Clinical outcome after MitraClip procedure: role of right ventricle. (14th October 2021) - Barosi, A; Gherbesi, E; Colombo, S; Giavarini, A; Cusmano, I; Colombo, A; Di Biasi, M; Viecca, M
Abstract: Background: MitraClip system is a device for percutaneous edge-to-edge repair of the mitral valve in symptomatic patients with severe mitral regurgitation (MR) not eligible for surgery, but frequently heart failure symptoms remain substantial on mid-term follow-up. Recently, right ventricular (RV) to pulmonary arterial (PA) coupling has emerged as a relevant prognostic predictor in heart failure but little is known about its prognostic role in patients after MitraClip implantation. Purpose: To identify echocardiographic predictors of clinical outcome after MitraClip procedure, with a particular focus on RV-PA coupling. Methods: We retrospectively analyzed the data of patients with severe MR who underwent MitraClip implantation between April 2015 and October 2019 at our Institution. Echocardiographic data were assessed at baseline, 3 and 12 months after the procedure; RV to PA coupling was assessed using the ratio between tricuspid annular plane systolic excursion (TAPSE) and pulmonary artery systolic pressure (PASP). Functional class was assessed at 12 months of follow-up. Significance level was set to 0.05 and SPSS was used for statistical analysis. Results: 41 patients were included (age 77.1±7.3, 71% male, BMI 25.8±5.5). MR was primary, functional and mixed in 22, 76 and 2% of patients, respectively. 1/2/3 mitraclips were implanted in 39/56/5% of patients, respectively. Echocardiographic data at baseline, at 3 and 12 months follow-up are shown in Table. NYHA class at 12 months significantly correlated with TAPSE and PASP at 3 months follow-up echocardiogram (beta coefficient −0.83 and 0.78 respectively). On the contrary, NYHA class did not show a correlation with left ventricular ejection fraction (LVEF) or residual MR grade. At 12 months 44% of patients showed an improvement in NYHA class; these patients had a better TAPSE (22.7±1.3 vs 19.4±4.6 mm), a lower PASP (37.9±10.2 vs 48.5±12.9 mmHg) and a better TAPSE/PASP (0.61±0.2 vs 0.42±0.2) compared to patients who did not improve their functional class, while LVEF and residual MR did not differ. Conclusion: In this sample of significant MR undergoing repair with MitraClip System, patients with functional class improvement at 12 months follow-up showed a better RV-coupling without difference in LV function and residual MR. Funding Acknowledgement: Type of funding sources: None.